Joint Venture for a New Product: A Matter of Trust - Maria Rosa Battagion; Paolo Garella (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
The paper establishes the effect of free-riding behavior by partners in a JV for a new product, when input to the JV are not verifiable. It then studies the ways in which the firms may control the incentives to free-ride and the effects that those agreements produce on the quality of the product, on profits, and on yhe welfare in the industry. Some Antitrust implications that justify existing tolerance by European Authorities towards JV's coorporation in sales and not only in research are finally derived.
Keywords: 330